A binary access control scheme with single key - Islam, Md. Rafiqul (Penerbit UTM Press, 1997)
An access control scheme for implementing the access control matrix is presented. The proposed scheme is based upon binary form of access rights and different from the schemes that are based on the concept of key-lock pairs. In this scheme each user is assigned one key. The keys are possessed by the user, and can be used to derive the access rights to the files. The scheme can easily handle the dynamic access control problem, such as changing access right, adding a user or file and deleting a user or file. This scheme is more effective and efficient for the systems where files are accessible to only limited number of users.